2016
DOI: 10.3389/fncel.2016.00287
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 Lysine 123 Acetylation in the Adult Central Nervous System

Abstract: Superoxide dismutase 1 (SOD1) knockout (Sod1−/−) mice exhibit an accelerated aging phenotype. In humans, SOD1 mutations are linked to familial amyotrophic lateral sclerosis (ALS), and post-translational modification (PTM) of wild-type SOD1 has been associated with sporadic ALS. Reversible acetylation regulates many enzymes and proteomic studies have identified SOD1 acetylation at lysine 123 (K123). The function and distribution of K123-acetylated SOD1 (Ac-K123 SOD1) in the nervous system is unknown. Here, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Glutathionylation, palmitoylation, succinylation and acetylation are among the PTMs of SOD1. Lysine 123 acetylation is a reversible PTM that regulates the interaction, subcellular localization, folding and activity of many proteins [ 48 ]. Specific conditions, such as H 2 O 2 and superoxide concentration, appear to favor SOD activity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathionylation, palmitoylation, succinylation and acetylation are among the PTMs of SOD1. Lysine 123 acetylation is a reversible PTM that regulates the interaction, subcellular localization, folding and activity of many proteins [ 48 ]. Specific conditions, such as H 2 O 2 and superoxide concentration, appear to favor SOD activity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin-1 is known to act as a deacetylase for SOD1 Lys70 and restores activation by hCCS (Lin et al ., 2015). Acetylation of Lys122, on the N-terminus of the electrostatic loop, does not change SOD1 activity but is found only in specific cell types and regions within the CNS indicating functional importance (Kaliszewski et al ., 2016). Non-specific lysine acetylation of wild-type, Asp90Ala and Ala4Val SOD1 with aspirin in vitro inhibited the nucleation rate and extension of aggregates overall.…”
Section: Secondary Sod1 Post-translational Modificationsmentioning
confidence: 99%
“…Figure 5B shows the increase in endogenous SOD1 succinylation at K122 in SIRT5-depleted cells. Although acetylation of K122 clearly occurs on endogenous SOD1 (21,26,28,30; also our proteomics data), our attempts to generate site-specific acetyl-K122 antibodies had only limited success: the antibodies showed marginal specificity to the acetylation. This complication, combined with the fact that K122E showed a slightly more robust effect in inhibiting the antirespiration function of SOD1 than K122Q, led us to focus primarily on K122 succinylation.…”
Section: Figmentioning
confidence: 77%
“…A study by Lin et al found that SIRT5 desuccinylates K122, and it was proposed to affect SOD1 antioxidant activity (29). In addition, a recent study using a site-specific antibody demonstrated that K122 is acetylated on endogenous SOD1 in multiple cell types throughout the murine nervous system (30), although the impact of the acetyl modification on SOD1 function was not demonstrated. With this background, we investigated the functional impact of K122 acylation on SOD1.…”
Section: Resultsmentioning
confidence: 99%